Providing micro-finance service for micro-enterprise: Performance of selected micro-finance institutions in Malaysia - Majid, Rahimah; Abdul Hakim, Roslan; Noor, Mohd Saifoul Zamzuri; Zainal Abidin, Faudziah (2007)
Like other developing countries, microfinance programs have been part of the poverty alleviation strategy in reaching the poor who are normally excluded from the formal credit sector. The inaccessibility of the poor to credit was mainly due to lack of good collateral or guarantors to qualify them for existing bank products. The microfinance programs as an approach taken to eradicate poverty is believed to be able in helping the poor to expand their economic activities and thus increase their income level as it open up the accessibility of the poor to credit. As such, to achieve its utmost impact on the poor, the development of effective and efficient microfinance institutions (MFIs) and improvement in the accessibility of the products and services provided by these institutions are crucial. This paper discusses the role and microfinance programs provided by two microfinance institutions in Malaysia, namely, the Bank Pertanian Malaysia (BPM) and Tabung Ekonomi Kumpulan Usaha Niaga (TEKUN). In specific, we examine their performance in terms of the products and services offered, delivery mechanism, outreach and its sustainability.